JSE 28:1 whole issue - Erickson, Kathleen E (Journal of Scientific Exploration, 2014)
TABLE OF CONTENTS Editorial 5  Editorial STEPHEN E. BRAUDE Research Articles 7  Stock Market Prediction Using Associative Remote Viewing by Inexperienced Remote CHRISTOPHER CARSON SMITH, DARRELL LAHAM, Viewers GARRET MODDEL 17  An Experimental Study for Reproduction of  Biological Anomalies Reported in the Hoeven 1999 Crop Circle ELTJO H. HASELHOFF, ROBERT J. BOERMAN, JAN-WILLEM BOBBINK 35  Pre-Columbian Transoceanic Infl uences: Far-Out Fantasy, Unproven Possibility, or Undeniable Reality? STEPHEN C. JETT Historical Perspective 75  G. Stanley Hall on “Mystic or Borderline Phenomena          CARLOS S. ALVARADO   Essay 95  Anomalistics, Pseudo-Science, Junk Science,Denialism: Corollaries of the Role of Science in Society HENRY H. BAUER Letter to the Editor 112  Exaggerated Emphasis      PETER A. MCCUE Book Reviews 113  UFOs, ETs, and Alien Abductions: A Scientist Looks at the Evidence by Don Donderi    THOMAS E. BULLARD 123  Time Loops and Space Twists: How God Created the Universe by Fred Alan Wolf        ALAN H. BATTEN 127  Science, the Self, and Survival After Death,Selected Writings of Ian Stevenson edited by Emily Williams Kelly ERLENDUR HARALDSSON 130  Essay Review: Medical Mysteries and Conundrums—When Doctors May Not Help. Understanding Hashimoto’s Encephalopathy: A Guide for Patients, Families, and Caregivers by Nicola Nelson, Susan Foley, and Shari Lawler for the Hashimoto’s Encephalopathy SREAT Alliance   HENRY H. BAUER 138  Thinking Fast and Slow by Daniel Kahneman TANA DINEEN 142  Dogmatism in Science and Medicine: How Dominant Theories Monopolize Research and Stifl e the Search for Truth by Henry H. Bauer      DONALD J. DEGRACIA 149  Dogmatism in Science and Medicine: How Dominant Theories Monopolize Research and Stifl e the Search for Truth by Henry H. Bauer      BRIAN JOSEPHSON 153  Science and the Afterlife Experience: Evidence for the Immortality of Consciousness by Chris Carter JAMES G. MATLOCK 160  Medical Qigong: Fact or Fiction? Chinese Medical Qigong edited by Tianjun Liu and Kevin W. Chen KENNETH S. COHEN Further Books of Note 172  The Man Who Filmed Nessie: Tim Dinsdale and the Enigma of Loch Ness by Angus Dinsdale  HENRY H. BAUER 173  Breaking Convention: A Multidisciplinary Conference on Psychedelic Consciousness edited by Cameron Adams, Anna Waldstein, Ben Sessa, David Luke, and David King      RICK STRASSMAN 174  Education in Parapsychology: Student and Instructor Perspectives by Harvey J. Irwin      CAROLINE WATT 175  Science and the Citizen: ContemporaryIssues and Controversies edited by Marco Mamone Capria HENRY H. BAUER SSE News 176  SSE Masthead 177  Index of Previous Articles in JSE 193  Order forms for JSE Issues, JSE Subscriptions, and Society Membership 196  SSE 33rd Annual Conference Announcement, San Francisco 198  SSE 10th Euro Conference Announcement, Leiden, The Netherlands 214  Instructions for JSE Authors